Synthesis, Characterization and Antimicrobial Properties of Schiff Bases Derived from Condensation of 8-Formyl-7-hydroxy-4-methylcoumarin and Substituted Triazole Derivatives - Kumar Sanjeev S. Lamani; Oblennavar Kotresh; Mohammed Shafi A. Phaniband; Jagannath C. Kadakol (E-Journal of Chemistry)
Two biologically active classes of compounds coumarins and triazoles were employed to form the Schiff bases. The synthesized Schiff base viz., 3-aryl-[(1-isocyano-4-methyl-7-hydroxycoumarin)]-5-methyl-1,3,4-triazoline-2-one and its substituents were obtained by the condensation of amino group of mono and disubstituted derivatives of 3-methyl-5-oxo-1,2, 4-triazoles with 8-formyl-7-hydroxy-4-methylcoumarin in alcohol. The characterization were studied by elemental analysis, IR, 1H NMR and mass spectra. The biological activities of the compounds were assayed against two bacterial via, B. subtilis, E.coli and two fungal strains A. niger, C.albican. The results indicate that the present compounds may serve as better fungicides when compared to bactericides. The synthesized compounds have turned to be wonder compounds possessing antimicrobial properties.